Leaching of Ca, K and Mg in a Dark-Red Latosol (LE) of "Cerrados" I. Magnitude and variability of the phenomenon under rainfall - Espinoza, Waldo; Reis, Antonio Eduardo G. dos (Pesquisa Agropecuaria Brasileira, 2014)
The leaching of Ca, K and Mg under rainfall in a LE soil Typic Haplustox)was evaluated by using porous cups at three depths: 30,75 and 105 cm during the growing cycle of corn (Zea mays L. cv. Cargill 111 -X) in 20 x 12 in plots that received low fertility treatments: corrective (AC) and maintenance (AM). Drainage and nutrient flux were shown to be rapid and dynamic suggesting that water movement took place mainly through the soil macrospores. Ca concentrations in soil solution were lower than the critical level of 1.0 mEq/lt and independent of the fertility treatments. Calcium losses due to leaching beyond 105 cm depth were estimated at 129 and 47 kg/ha in plots AC and AM, equivalent to 6.1 and 2.5% of the total Ca initially added, respectively. Potassium concentrations in the soil solution ranged from 0.05 to 0.25 mEq/lt, and leaching losses at the 105 cm depth reached 67.5 and 14,7 kg/ha K for AC and AM plots, which represents 48.21 and 36.75% of the initially applied K, respectively, A close relationships was found between drainage flux at the 105 cm depth and amount of leached K. As the drainage flux increased in magnitude, K concentration decreased. Magnesium concentrations in the soil solution ranged from 0.08 to 0.5 mEq/lt and leaching losses were estimated as 96.0 and 19.8 kg/ha for plots AC and AM, respectively. In the AM plot (considered normal), losses represented 72% of the Mg added in the liming materials. The accumulated leaching curves for the different nutrients showed a close relationship to the accumulated rainfall curves.